Kinetics of photoelectrochemical oxidation of methanol on hematite photoanodes - Mesa,Zamora CA; Kafizas,A; Francàs,L; Pendlebury,S; Pastor,E; Ma,Y; Le,Formal F; Mayer,M; Grätzel,M; Durrant,J (Journal of the American Chemical Society, 2017)
The kinetics of photoelectrochemical (PEC) oxidation of methanol, as a model organic substrate, on α-Fe2O3 photoanodes are studied using photoinduced absorption spectroscopy and transient photocurrent measurements. Methanol is oxidized on α-Fe2O3 to formaldehyde with near unity Faradaic efficiency. A rate law analysis under quasi-steady-state conditions of PEC methanol oxidation indicates that rate of reaction is second order in the density of surface holes on hematite and independent of the applied potential. Analogous data on anatase TiO2 photoanodes indicate similar second-order kinetics for methanol oxidation with a second-order rate constant 2 orders of magnitude higher than that on α-Fe2O3. Kinetic isotope effect studies determine that the rate constant for methanol oxidation on α-Fe2O3 is retarded ∼20-fold by H/D substitution. Employing these data, we propose a mechanism for methanol oxidation under 1 sun irradiation on these metal oxide surfaces and discuss the implications for the efficient PEC methanol oxidation to formaldehyde and concomitant hydrogen evolution.